Single-qubit rotation gate using three-level lambda systems - Issoufa, Youssouf Hamidou; Messikh, Azeddin (INSI Publications, 2011)
In this paper we investigate the effect of time separation and delay between two f-STIRAP on single-qubit rotation gate based on Lacour et al (2006 Opt. Commun. 264 362). The f-STIRAP is a basic method used to adiabatically transfer population between lower states, where the two pulses terminate simultaneously while maintaining a constant ratio of amplitudes. Furthermore, we obtain numerically the optimal values for the time separation and delay for a perfect single-qubit rotation gate.